GAMBARAN PENERAPAN SBAR DAN TULBAKON DALAM KOMUNIKASI INTERDISIPLINER (STUDI PENELITIAN DI RSUD RATU ZALECHA MARTAPURA) - Marantika, Dyci; Pertiwiwati, Endang; Setiawan, Herry (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2018)
SBAR is a technique of communication among the medical team about the condition of patient,especially critical condition which needed a direct an action. Meanwhile Tulbakon is averification process on the accuracy of oral communication quickly. The good implementation ofSBAR and Tulbakon in interdisciplinary communication are able to increase the salvation ofpatient. To know the description of the application of SBAR and Tulbakon on the interdisciplinarycommunication at RSUD Ratu Zalecha Martapura. Description research of 43 respondents atVIP Intan ward and Assami wardat RSUD Ratu Zalecha Martapura. Based on the result of theresearch found the whole description of the application of SBAR shows that 76,7% respondentsincluded in very good category, 21,0% respondents included in good category , and 2,3%respondents included in adequate category. The description of the whole application ofTulbakonshows that 46,5% respondents included in very good category, 41,9% respondents included ingood category, and 11,6% respondents included in adequate category. The description of theapplication of SBAR and Tulbakon are believed both SBAR and Tulbakon can increase thesalvation of patient. The loyalty on the SOP has been already used well, yet it would be better ifall of the nurses apply its based on the SOP hospital.